Cuthbert Tunstall, Tyndale's 'Still Saturn'. Issue 1 (3rd July 2014) - Clark, Margaret
Abstract : Cuthbert Tunstall was lampooned by William Tyndale as the 'still Saturn', a nickname that persisted in polemical use to the end of Tunstall's career. His own humanist circle saw him in a very different light, praising him as a pleasant companion where Tyndale saw him as a brooding malevolence. There is some justification for the polemical abuse, but an investigation into the varying significance of Saturn in contemporary thought suggests its greatest accuracy occurred in an unexpected form. Saturn, although generally seen as malevolent, could also rule the Age of Gold. Tyndale obviously meant the pejorative sense; Tunstall's Marian diocese thought differently. Tunstall's great crimes were the searching out and burning of heretical books, and his humane approach to the burning of heretics. Tyndale's accusation arose from disappointment at Tunstall's failure to sponsor his New Testament translation, which in the circumstances seems understandable.